2022
DOI: 10.1002/adfm.202210322
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Modulation of Metal–Organic Frameworks by Interfacial Bridging for Efficient pH‐Universal Hydrogen Evolution

Abstract: Designing well-defined interfacial chemical bond bridges is an effective strategy to optimize the catalytic activity of metal-organic frameworks (MOFs), but it remains challenging. Herein, a facile in situ growth strategy is reported for the synthesis of tightly connected 2D/2D heterostructures by coupling MXene with CoBDC nanosheets. The multifunctional MXene nanosheets with high conductivity and ideal hydrophilicity as bridging carriers can ensure structural stability and sufficient exposure to active sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 57 publications
(57 reference statements)
1
46
0
Order By: Relevance
“…Different M-O-M units can establish interfacebonding channels to enhance charge transfer, modulate the charge state of the surface adsorbate to activate reaction intermediates, and mediate the selectivity or activity of hybrid catalysts involving multiple transition pathways. [16][17][18][19][20] Therefore, searching for a matching M-O-M bond is a potentially effective solution to improve the synergistic catalytic performance. Considering that Fe 2 O 3 possesses half-fully occupied 3d orbitals and a flexible spin state, the construction of Ni-O-Fe pairs might well generate directional electron transfer from Ni-3d to Fe-3d orbitals, which consequently results in a strong interaction at the oxide interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Different M-O-M units can establish interfacebonding channels to enhance charge transfer, modulate the charge state of the surface adsorbate to activate reaction intermediates, and mediate the selectivity or activity of hybrid catalysts involving multiple transition pathways. [16][17][18][19][20] Therefore, searching for a matching M-O-M bond is a potentially effective solution to improve the synergistic catalytic performance. Considering that Fe 2 O 3 possesses half-fully occupied 3d orbitals and a flexible spin state, the construction of Ni-O-Fe pairs might well generate directional electron transfer from Ni-3d to Fe-3d orbitals, which consequently results in a strong interaction at the oxide interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution XPS spectra of Co 2p (LMM: 774.87 eV; 2p 3/2 : 781.22 eV; 2p 1/2 : 797.17 eV) and Ni 2p (2p 3/2 : 856.03 eV; 2p 1/2 : 873.63 eV) in Ni,Co–FeOOH/CC correspond to typical Co­(II)–OH and Ni­(II)–OH, confirming that the doping with Co and Ni replaces Fe in the form of divalent cations (Figure e,f). The positions of the characteristic peaks of Co 2p and Ni 2p in Ni,Co,Yb–FeOOH/CC do not shift compared with Ni,Co–FeOOH/CC, indicating that Co and Ni remain the divalent cation after doping with Yb.…”
Section: Resultsmentioning
confidence: 62%
“…After the OER cycling, the nanosheet structure of IF-Ni 150 mM is well preserved, further confirming the favorable electrochemical durability of the catalyst (Figure S18, SI). 53 The roughening of the outer edges can be attributed to partial electro-oxidation at high voltages. In addition, the IF-Ni 150 mM nanosheets showed distinct lattice streaks at the edges after the durability test attributed to the (102) crystal plane of hydroxy nickel oxide, which was consistent with the XRD result (Figures S19 and S21 (EDX) spectra presented obvious Fe, Ni, and O signals, and elemental mapping revealed that these species were uniformly distributed in the entire catalyst (Figure S20).…”
Section: Resultsmentioning
confidence: 99%